Trauma Reactivation Plus Propranolol is Associated with Durably Low Physiological Responding during Subsequent Script-Driven Traumatic Imagery. (April 2014) - Brunet, Alain; Thomas, Émilie; Saumier, Daniel; Ashbaugh, Andrea R; Azzoug, Abdelmadjid; Pitman, Roger K; Orr, Scott P; Tremblay, Jacques
Objective: In a previous, double-blind, placebo-controlled study, patients with posttraumatic stress disorder (PTSD) showed lower physiological response during script-driven traumatic imagery 1 week after receiving a single dose of propranolol given after the retrieval of a traumatic memory. We hypothesized that this effect would extend beyond 1 week using a modified treatment approach. Method: Twenty-eight participants with PTSD read an account of their traumatic event once weekly for 6 consecutive weeks under the influence of open-label propranolol. One week and 4-months later, skin conductance, heart rate, and left corrugator electromyogram responses were measured while participants engaged in script-driven mental imagery of their traumatic event. Results from the 22 study participants were compared with results from treated and untreated participants in a previously published trial. Results: Most participants in our study were classified as non-PTSD cases at posttreatment and follow-up according to a psychophysiological discriminant function analysis. Posttreatment skin conductance and heart rate responses of the current (propranolol-treated) participants were lower than those of placebo participants from the previous study. No difference was observed between physiological responding measured posttreatment and at follow-up. Conclusions: Low physiological responding during script-driven traumatic imagery after treatment extends up to 4 months, demonstrating the durability of the treatment effect's. Limitations include the absence of a placebo-controlled group and lack of physiological baseline measures. Despite these limitations, results point to the need for future trials examining the clinical efficacy of trauma reactivation plus propranolol, as it has the potential to become a novel, cost- and time-effective treatment for PTSD.